2018
DOI: 10.18332/tid/90004
|View full text |Cite
|
Sign up to set email alerts
|

Association of active/passive smoking and urinary 1-hydroxypyrene with poor sleep quality: A cross-sectional survey among Chinese male enterprise workers

et al.

Abstract: INTRODUCTION Tobacco use has been implicated as an important factor for poor sleep quality. However, in most studies, the sleep quality of smokers was only assessed though a self-reported questionnaire, without measuring any internal biomarkers that reflect the levels of tobacco exposure. We examined the association of active and passive smoking with sleep quality, assessed smoking exposure using urinary 1-hydroxypyrene (1-HOP) as an internal biomarker, and further explored the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Smoking negatively affects some physiological parameters during sleep, including sleep architecture and nocturnal oxygenation. Previous studies by Jaehne et al 21 and Zhou et al 22 have shown that smoking prolongs SL. Another study by Casasola et al 8 suggested that smoking reduces the oxygen saturation of healthy people at night.…”
Section: Discussionmentioning
confidence: 87%
“…Smoking negatively affects some physiological parameters during sleep, including sleep architecture and nocturnal oxygenation. Previous studies by Jaehne et al 21 and Zhou et al 22 have shown that smoking prolongs SL. Another study by Casasola et al 8 suggested that smoking reduces the oxygen saturation of healthy people at night.…”
Section: Discussionmentioning
confidence: 87%
“…Besides, smoking yields of PAH compounds have been shown to vary considerably based on the type of cigarette, genetic variability and individual differences in PAH metabolizing enzymes and smoking pattern ( 26 ). However, CS has been shown to induce a 16% increase in urinary 1-HOP excretion and active smokers have been reported to have higher urine levels of 1-HOP than non-smokers ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking is not only a risk factor for elevation of pain severity, but also a risk factor for sleep disturbances. [38][39][40] Therefore, the relationship between preoperative poor sleep quality and postoperative pain is complex in smokers. Consequently, the relationship between sleep and pain in smokers cannot be concluded in our study.…”
Section: Discussionmentioning
confidence: 99%